2019
DOI: 10.1111/mpp.12821
|View full text |Cite
|
Sign up to set email alerts
|

The plant hypersensitive response: concepts, control and consequences

Abstract: Summary The hypersensitive defence response is found in all higher plants and is characterized by a rapid cell death at the point of pathogen ingress. It is usually associated with pathogen resistance, though, in specific situations, it may have other consequences such as pathogen susceptibility, growth retardation and, over evolutionary timescales, speciation. Due to the potentially severe costs of inappropriate activation, plants employ multiple mechanisms to suppress inappropriate activation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
277
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(318 citation statements)
references
References 177 publications
5
277
0
6
Order By: Relevance
“…Interestingly, earlier studies demonstrated that loss of the chloroplast protein Les22, a uroporphyrinogen decarboxylase involved in chlorophyll biosynthesis, results in spontaneous lesions that resemble an HR [43]. This example with the Les22 protein is characteristic of the phenomenon observed in lesion mimic mutants of several plant species (e.g., rice, maize and the model plant Arabidopsis) in which spontaneous HR like symptoms, the hallmark of ETI, are observed without a pathogen being present [44]. Lesion mimic mutations have also been identified in the maize (ZmLls1) and wheat (TaLls1) genes encoding pheophorbide a oxygenase (PaO) for chlorophyll breakdown [45].…”
Section: Chloroplast Pigments and Carbohydrate Metabolismmentioning
confidence: 96%
“…Interestingly, earlier studies demonstrated that loss of the chloroplast protein Les22, a uroporphyrinogen decarboxylase involved in chlorophyll biosynthesis, results in spontaneous lesions that resemble an HR [43]. This example with the Les22 protein is characteristic of the phenomenon observed in lesion mimic mutants of several plant species (e.g., rice, maize and the model plant Arabidopsis) in which spontaneous HR like symptoms, the hallmark of ETI, are observed without a pathogen being present [44]. Lesion mimic mutations have also been identified in the maize (ZmLls1) and wheat (TaLls1) genes encoding pheophorbide a oxygenase (PaO) for chlorophyll breakdown [45].…”
Section: Chloroplast Pigments and Carbohydrate Metabolismmentioning
confidence: 96%
“…Cell death triggered by ETI is often considered as a part of the defence response resulting in suppression of disease progress (Balint-Kurti, 2019). In general, some other immune responses may precede this exhibition, including ROS accumulation, callose deposition, and changes in levels of phytohormones (Asai and Yoshioka, 2009;Deb et al, 2018;Bürger and Chory, 2019).…”
Section: Expression Of Plavh142 Activates Various Immune Responsesmentioning
confidence: 99%
“…One of the earliest hallmarks of HR is the rapid and intense production of reactive oxygen species (ROS) [57]. In Ny-1-mediated resistance of cv.…”
Section: Hypersensitive Response-mediated Resistance: Response At Thementioning
confidence: 99%